Alimentação e ambiente alimentar no território do programa Academia da Saúde de Belo Horizonte, Minas Gerais - Bruna Vieira de Lima Costa (2015)
Two studies, one cross-sectional and other ecological, were carried out in the Health Academy Program (HAP) of Belo Horizonte, Minas Gerais. HAP is a focus point of the Brazilian Unified Health System to promote health through actions such as regular physical exercise and healthy eating. In the cross-sectional study, we aimed to identify the nutritional status and health conditions of individuals entering in the HAP, over a three year period, in a reference site of the Program. Were registered sociodemographic data, health conditions, food intake and anthropometry. On the other hand, the ecological study evaluated stores selling groceries confined in buffers from 18 sites of the Program selected by simple conglomerate sampling strategy, stratified according to the nine administrative regions of the city. Data from the stores were obtained with the city administration. In each store were registered, by direct observation, variables as the type and location of establishments, availability, variety and advertising of fruit and vegetables (FV) and ultraprocessed foods, allowing estimating a quality index of access to food in the shops (IAFE). To verify the association between sociodemographic variables (education and income) and the type of commercial establishment, with the IAFE, HAP users residing in a radius of a 1,000m these establishments were selected. In the cross-sectional study, we found that HAP users had lower education and income, high prevalence of dietary inadequacies, such as low intake of FV (75.3%), and diseases such as hypertension and overweight. These findings indicate the need for assessing the food environment in the area of HAP. Thus, we proceeded to conduct the environmental study. From the 1,211 establishments initially identified, 385 were excluded for not commercializing FV and 72 for being duplicates in the City Hall list. A total of 754 stores were then visited. From this,46.3% (n = 349) were inexistent or inoperable and 23% (n = 172) did not commercialize FV. Of the remaining 233 stores, 13% (n = 31) refused to participate. However, establishments found spontaneously (n = 127) were also included, of which 11% (n = 14) refused to participate. A final number of 336 sites were analyzed. Most centers were not located in regions with the highest density of shops and only one-sixth of the hot areas had establishments with better access to FV. The median IAFE was 11 (5-16), and the establishments located closest to residential users (median: 319m) were mostly green groceries and street grocery markets. The IAFE was influenced by the type of establishment, and the increase of 1% in the frequency of green groceries/street grocery markets and supermarkets was associated with an increase of 0.12 and 0.07 point in the IAFE, respectively. The results point to the importance of implementing policies supporting the supply of healthy foods prioritizing intersectoral action in areas with low access to these items, allowing the construction of a healthy environment. This would improve access, availability and consumption of healthy foods, such as FV, in the population and thus contribute to overcoming health inequities. Furthermore, HAP, as a health promotion site, can have its food and nutrition education activities strengthened by the healthy territory.